Early life stages of the snapping shrimp Alpheus cf. packardii: morphological description of the first three zoeal stages - Sanches, Nádia de Moraes [UNESP]; Costa, Rogerio Caetano [UNESP]; Pescinelli, Régis Augusto (Taylor & Francis, 2024)
The morphology of the zoeae I, II and III of Alpheus cf. packardii was described based on laboratory-hatched larvae. Parental female was captured at Ubatuba bay, north coast of São Paulo, Brazil. The morphological characteristics of the species were compared with descriptions of other Alpheus species with known first zoeal stages. The zoea I of A. cf. packardii differs from the other 27 species through: coxal endite of maxillule with 6 (4 simple, and 2 sparsely plumose) setae; basal endite with 2 stout spines, 1 small plumose setae and 1 small simple setae; coxal endite of maxilla not bilobed, with 2 long sparsely plumose setae; basal endite bilobed, proximal lobe 2 simple and 1 sparsely plumose setae, distal lobe with 2 simple setae and 1 sparsely plumose setae, both with one terminal protuberance; second maxilliped with endopod 4-segmented, 1 terminal simple, 0, 1 terminal serrate, 5 (1 proximal and 3 terminal simple, plus 1 terminal serrate) setae. Considering the importance of the identification of larval forms in the natural environment, our results can be used in a larval identification key and help to advance research on areas such as ecological distribution of early post-embryonic stages in the meroplankton community.
Keywords: Decapoda; intertidal; larval development; zoea